Toxic effects of low doses of methyl-tertiary butyl ether on hematological indices in the male rats - Ahmad Badr (Shiraz University of Medical Sciences, 2019)
Methyl-tertiary butyl ether (MTBE), as a fuel additive is added to reformulated gasoline to enhance octan number and air quality. The aim of this study was to investigate the effect(s) of low doses of MTBE on some hematological indices in the male rats. In this study, two separate experiments (A and B) were conducted. In experiment A, the rats were randomly divided into 2 equal (n=5) groups that recived 0 and 10 mg MTBE/kg/day in tap water by gavage for 28 consecutive days. In experiment B, animals were assigned into two equal groups (n=5) that recived 0 and 1 mg MTBE/kg/day for 10 consecutive days. At the end of the exposure period, the white blood cell count (WBC), red blood cell (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpusular volume (MCV), mean corpusular hemoglobin (MCH), mean corpusular hemoglobin concentration (MCHC) and platelet count (PLT) were determined. Statistical analysis revealed that, there was a significant alteration in MCHC between control and treatment groups (P<0.05) in experiment A. No changes were observed for the other blood parameters. Also, in experiment B, the means of WBC, MCH and MCHC showed significant differences between groups (P<0.05). In conclusion,the present study showed that exposure to low and very low levels of MTBE can alter some hematological indices in the male rats.